Flavonoids supplementation - an ideal approach to improve quality of poultry products - Kamboh, A. A.; Leghari, R. A.; Khan, M. A; Kaka, U.; Naseer, M.; Sazili, A. Q.; Malhi, K. K. (Gorgan University of Agricultural Sciences and Natural Resources, 2019)
Supplementing flavonoids in poultry diets has shown the potential to progress the nutritional, sensorial and microbiological quality of poultry meat and eggs. In the last decade, several studies have determined the benefits of flavonoids for inhibition of lipid oxidation and microbial growth, check any pH-dependent deterioration and improve the colour stability of meat and related products. Flavonoids are typically absorbed in the ileum where pH is between 5-6.8. The various flavonoids vary in effective dose levels in poultry, but are typically included in levels ranging from 0.05-0.2%. Furthermore, flavonoid supplementation in the chicken diet has been reported to positively alter the fatty acid profile of meat and eggs by reducing the cholesterol and triglyceride content. Meat colour, in terms of lightness, can be improved by up to 5%. The aim of this review is to evaluate the use of various plant flavonoids as a substitute for synthetic feed additives in the poultry feed industry to satisfy consumer demands in terms of quality and safety of animal products. The results have stimulated interest in more research on the various flavonoid classes to determine the most effective compounds and their optimal doses for both broilers and laying hens.